2007
DOI: 10.1080/00224490701263868
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Women's Sexuality in China since 1980: A Critical Review

Abstract: Over the last 20 years, women's sexuality has become one of the most written about and intensely debated subjects in sexology, sociology and women's studies in mainland China. From these studies, one can trace the development of academic discourse on women's sexuality through three distinct phases: from a predominantly medical discourse, to the use of survey methods to investigate women's real experiences, and finally to a phase in which Western theories have become increasingly influential. Each phase feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 15 publications
0
10
1
Order By: Relevance
“…The findings of this study are in sharp contrast with past research on female sexuality in China which reported markedly conservative sexual norms compared to those found in our study (Li, 1997; Pei et al, 2007; Liu, 1992). Though a few qualitative studies focused on a more open attitude and behaviors among younger white collars females in urban areas (Huang, 2008; Pei, 2007; Zhang, 2007), the results have not reached women of lower social status.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The findings of this study are in sharp contrast with past research on female sexuality in China which reported markedly conservative sexual norms compared to those found in our study (Li, 1997; Pei et al, 2007; Liu, 1992). Though a few qualitative studies focused on a more open attitude and behaviors among younger white collars females in urban areas (Huang, 2008; Pei, 2007; Zhang, 2007), the results have not reached women of lower social status.…”
Section: Discussioncontrasting
confidence: 99%
“…Only a few of these works focus on women’s sexuality (Harriet, 1997; Li,1994; Huang, 2008; Pei, Ho & Ng, 2007). …”
Section: Introductionmentioning
confidence: 99%
“…A possible explanation is that the portrayal of nudity in public is seen as more inconsistent with existing cultural stereotypes and cultural identity in Asia than in Western Europe. Though it is changing, the stereotype of oppressed and obedient Chinese women still prevails, both among Chinese (Yuxin, Petula, and Lu 2007) and Westeners (Yu-Ning 2015). Likewise, individuals with a European background were found to be less restrictive in their attitudes toward sexuality than people with Asian ancestry Gorzalka 1996, 1998).…”
Section: Cultural Identity Theory and Offensive Nudity Advertisingmentioning
confidence: 99%
“…Pei Yuxin characterizes the emergence of sex research in China in the postCultural Revolution, Deng Xiaoping era of the early 1980s, as the 'medical' period, focused on sexual 'health' and translations of Western texts (Pei 2007 Johnson is seen by some as legitimizing perversion and unleashing the excesses of the sexual liberation movement of the 60s. Liu Dalin, who like Kinsey, uses the survey instrument to hold up a mirror to society and as a counter discourse to official propaganda, is also more of a moralist than Kinsey, warning that sexual permissiveness is linked to the explosion of rape, prostitution, and bigamy.…”
Section: History Of Chinese Sexologymentioning
confidence: 99%